2007
DOI: 10.1002/art.22672
|View full text |Cite
|
Sign up to set email alerts
|

A multiethnic, multicenter cohort of patients with systemic lupus erythematosus (SLE) as a model for the study of ethnic disparities in SLE

Abstract: Objective. To examine health disparities as a function of ethnicity using data from LUpus in MInorities, NAture versus nurture (LUMINA), a longitudinal study of patients with systemic lupus erythematosus (SLE); to build an explanatory model of how ethnic disparities occur in this setting; and to suggest appropriate interventions. Methods. LUMINA patients (meeting American College of Rheumatology criteria for SLE) ages >16 years of African American, Hispanic (from Texas), Hispanic (from Puerto Rico), or Caucasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
224
3
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(258 citation statements)
references
References 52 publications
15
224
3
8
Order By: Relevance
“…Conversely, environmental, socioeconomic/demographic, psychosocial, genetic, and clinical factors were thought to play an important role as determinants of ethnic differences observed in LN outcome. 24 Socioeconomic and medical factors were largely controlled in the trial setting, and socioeconomic data were not recorded as part of this study; consequently, the impact of socioeconomic factors on the efficacy of therapeutic interventions for LN remains to be determined. The results of this study may support the clinical impression that the efficacy of IVC varies between racial and ethnic groups and that IVC is less effective in patients of African or Hispanic descent.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, environmental, socioeconomic/demographic, psychosocial, genetic, and clinical factors were thought to play an important role as determinants of ethnic differences observed in LN outcome. 24 Socioeconomic and medical factors were largely controlled in the trial setting, and socioeconomic data were not recorded as part of this study; consequently, the impact of socioeconomic factors on the efficacy of therapeutic interventions for LN remains to be determined. The results of this study may support the clinical impression that the efficacy of IVC varies between racial and ethnic groups and that IVC is less effective in patients of African or Hispanic descent.…”
Section: Discussionmentioning
confidence: 99%
“…These diverse presentations appear to be multifactorial. It is reported that socioeconomic, environmental, demographic, psychosocial and genetic factors may play an important role as determinants of ethnic differences in clinical manifestations of SLE patients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatol. (2018) 13 (3) subjective quality of life symptoms are among the most common problems reported by patients with SLE [17].…”
Section: Research Articlementioning
confidence: 99%